Preparation method of PET (Polyethylene Terephthalate) composite film

By corona treatment of the PET film surface and roll coating with PVB adhesive, combined with silane coupling agent and light-transmitting filler, the problem of low bonding between PET and PVB was solved, and a PET composite film with good flexibility and dimensional stability was prepared, thus avoiding the breakage of photovoltaic cells.

CN120816736APending Publication Date: 2025-10-21JIAXING FUYING COMPOSITE MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511022342.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-24
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

In existing photovoltaic cell encapsulation, the bonding between flexible films such as PVB and PET is not high, making them prone to cracking and causing solar cells to break.

Method used

By corona treatment of the PET film surface to increase polar groups, followed by roll coating with PVB adhesive and the addition of silane coupling agent and light-transmitting filler, the bonding strength and flexibility of PET and PVB are improved.

Benefits of technology

The prepared PET composite film has good flexibility and dimensional stability, reduces the risk of cracking, and improves the overall performance of the encapsulation film.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of a PET composite film, and belongs to the technical field of photovoltaic packaging assemblies. The preparation method of the PET composite film comprises the following steps: carrying out corona on the surface of the PET film; roller-coating a PVB (Polyvinyl Butyral) adhesive and drying; and hot-pressing and compounding with a flexible packaging adhesive film. The PVB adhesive contains a silane coupling agent of which the content is less than 10wt%. Particularly, when the silane coupling agent contains an amino group or an isocyanate group and the dosage of the silane coupling agent is 0.09-1.5 wt%, the bonding strength between the PET film and the flexible packaging adhesive film can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a PET composite film, and belongs to the technical field of photovoltaic packaging components. Background Art

[0002] In existing technologies, photovoltaic cell encapsulation typically involves coating both sides of a solar panel with flexible films such as EVA and PVB. Solar glass and a backsheet are then added to each side. Finally, the overall structure is edge-sealed with an aluminum alloy frame. Flexible films like PVB expand and contract significantly with heat and cold, which can easily cause the solar cells to break under ambient conditions. Despite these drawbacks, the elastic and soft nature of encapsulation films is essential; otherwise, they would break during packaging or transportation. Therefore, existing technologies typically employ a composite method to improve the dimensional stability of encapsulation films.

[0003] Although PET lacks flexibility and has high water vapor permeability, it possesses excellent toughness and dimensional stability. It also exhibits excellent heat and cold resistance, is less susceptible to thermal expansion and contraction, and offers excellent electrical insulation and transparency. Therefore, current composite packaging films primarily use PET as a base film, with a flexible adhesive layer such as PVB or EVA layered on top. However, PVB and EVA films do not bond well with PET, making interlayer cracking a common problem. Once cracked, the flexible film's dimensional stability becomes difficult to maintain, potentially leading to problems such as solar cell fragmentation. Summary of the Invention

[0004] The present invention aims to solve the above problems and thus provides a method for preparing a PET composite film. The PET composite film prepared according to the method of the present invention has the advantages of good flexibility, high dimensional stability, and low cracking.

[0005] The technical solutions of the present invention for solving the above problems are as follows:

[0006] The preparation method of the PET composite film comprises the following steps:

[0007] S1. Providing a PET film, and performing surface corona treatment on one or both sides of the PET film;

[0008] S2, the corona treated surface of the PET film is roll-coated with PVB adhesive, followed by drying;

[0009] S3, hot-pressing and laminating one or both sides of the PET film with a flexible encapsulation film to obtain a PET composite film;

[0010] The PVB adhesive comprises the following components in parts by mass:

[0011] PVB 5~20 parts

[0012] Silane coupling agent 0.3~10 parts

[0013] 90-100 parts of solvent;

[0014] The solvent is selected from one or more of methanol, ethanol, butanone, propylene glycol methyl ether, propylene glycol methyl ether acetate, and toluene;

[0015] The PVB has a hydroxyl content of 8-20% and a polymerization degree of 499-2499.

[0016] PET, short for polyethylene terephthalate, is a thermoplastic material. Its molecular structure contains numerous repeating segments: -[-CO-C6H4-CO-O-CH2-CH2-O-]-. These segments, formed by the esterification of terephthalic acid and ethylene glycol, are highly rigid and contribute to PET's exceptional toughness and dimensional stability. In the above technical solution of the present invention, the surface of the PET film is subjected to corona treatment, which can interrupt some chain segments -[-CO-C6H4-CO-O-CH2-CH2-O-]- on the surface of the film, thereby generating a large number of active groups such as hydroxyl and carboxyl groups on the surface of the PET film, thereby significantly improving the surface polarity of the PET film; then, the roller-coated PVB adhesive contains, in addition to a PVB resin having a degree of polymerization of 499 to 2499, a silane coupling agent. The silane coupling agent can not only combine with the active groups in the PVB resin, but also be compatible with the non-polar main chain of the PET film, thereby improving the adhesion of the PVB adhesive to the PET surface; and, since a large number of polar groups are generated on the surface of the PET film due to the corona treatment, these polar groups can also be compatible with or further combine with the active groups in the PVB resin, thereby further improving the adhesion of the PVB adhesive to the PET surface.

[0017] As a preferred embodiment of the above technical solution, the PVB adhesive further contains 2 to 30 parts by mass of a light-transmitting filler, and the light-transmitting filler is selected from one or more of transparent glass flakes, PPO film flakes, transparent ceramics, glass powder, glass fiber, transparent montmorillonite, transparent mica, fumed silica, amorphous silica, quartz sand, quartz powder, nano-silica, zeolite, transparent alumina ceramics, magnesium oxide transparent ceramics, yttrium oxide transparent ceramics, aluminum magnesium spinel transparent ceramics, aluminum nitride transparent ceramics, aluminum oxynitride transparent ceramics, transparent PLZT electro-optical ceramics, yttrium aluminum garnet laser transparent ceramics, and transparent scintillating ceramics.

[0018] In the above-mentioned technical solution of the present invention, the addition of fillers can improve the water vapor transmission rate of the overall composite film; and because the fillers are transparent, they have little effect on the light transmittance of the composite film. In particular, when the transparent fillers have a shimmering effect, they can produce a dazzling effect while ensuring light transmission, such as in PPO film flakes and transparent shimmering ceramics.

[0019] As a preferred embodiment of the above technical solution, when the light-transmitting filler is spherical, the particle size is 10-800 μm; when the light-transmitting filler is flake-shaped, the flake diameter is 10-4000 μm and the thickness is 1 nm-30 μm.

[0020] As a preferred embodiment of the above technical solution, the mass amount of the light-transmitting filler is 2 to 10 parts.

[0021] As a preferred embodiment of the above technical solution, the silane coupling agent is selected from one or more of amino silane coupling agents, isocyanate silane coupling agents, and carbamate silane coupling agents.

[0022] As a preferred embodiment of the above technical solution, the amino-based silane coupling agent has one to three amino groups, and the amino groups are primary, secondary or tertiary amino groups.

[0023] As a preferred embodiment of the above technical solution, the coating thickness of the PVB adhesive is 10-800 μm.

[0024] As a preferred embodiment of the above technical solution, the flexible packaging film is selected from one of PVB film, EVA film or POE film.

[0025] As a preferred embodiment of the above technical solution, in step S1, the output power of the corona treatment equipment is 2-6 kW, and the treatment time is 15-30 min.

[0026] As a preferred embodiment of the above technical solution, in step S2, the drying temperature is 85-110°C, and the drying time is 5-10 minutes.

[0027] As a preferred embodiment of the above technical solution, in step S3, the hot pressing temperature is 100-150° C., the pressure is 0.5-2.0 MPa, and the hot pressing time is 30-100 s.

[0028] In summary, the present invention has the following beneficial effects:

[0029] 1. The present invention uses an online roller coating scheme to prepare a PET composite film, and simultaneously develops a PVB adhesive suitable for online roller coating; this has the advantage of having a good composite effect between the encapsulating film and the PET base film;

[0030] 2. The PVB adhesive suitable for online roller coating of the present invention comprises a PVB resin having a hydroxyl content of 8 to 20% and a degree of polymerization of 499 to 2499, and a specific silane coupling agent. The silane coupling agent can not only combine with the active groups in the PVB resin, but also be compatible with the non-polar main chain of the PET film, thereby improving the adhesion of the PVB adhesive to the PET base film;

[0031] 3. The preparation method of the present invention further performs a surface corona treatment on the PET film before roller coating the adhesive, which can generate a large number of polar groups on the surface of the PET film. These polar groups can also be compatible with or further combined with the active groups in the PVB resin, thereby further improving the adhesion of the PVB adhesive to the PET surface;

[0032] 4. In a preferred embodiment, the PVB adhesive of the present invention further contains a transparent filler to reduce the water vapor permeability of the composite film;

[0033] 5. In a more preferred embodiment of the PVB adhesive of the present invention, the transparent filler may be PPO film flakes or transparent scintillating ceramics, which not only maintains the transparent property but also enables the composite film to have a colorful feature. DETAILED DESCRIPTION

[0034] The present invention is further explained below.

[0035] This specific implementation is merely an explanation of the present invention and is not intended to limit the present invention. Any changes made by those skilled in the art after reading the specification of the present invention will be protected by patent law as long as they are within the scope of the claims.

[0036] Example 1

[0037] The preparation method of the PET composite film comprises the following steps:

[0038] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0039] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0040] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0041] The PVB adhesive comprises the following components in parts by mass:

[0042] PVB 10 parts

[0043] 2 parts of silane coupling agent

[0044] 100 parts of propylene glycol methyl ether;

[0045] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0046] The silane coupling agent is triethoxysilyl undecane, and its CAS number is 116047-42-8.

[0047] Example 2

[0048] The preparation method of the PET composite film comprises the following steps:

[0049] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0050] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0051] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0052] The PVB adhesive comprises the following components in parts by mass:

[0053] PVB 10 parts

[0054] 2 parts of silane coupling agent

[0055] 100 parts of propylene glycol methyl ether;

[0056] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0057] The silane coupling agent is (3-aminopropyl)trimethoxysilane, with a CAS number of 13822-56-5.

[0058] Example 3

[0059] The preparation method of the PET composite film comprises the following steps:

[0060] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0061] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0062] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0063] The PVB adhesive comprises the following components in parts by mass:

[0064] PVB 10 parts

[0065] 2 parts of silane coupling agent

[0066] 100 parts of propylene glycol methyl ether;

[0067] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0068] The silane coupling agent is 11-allyloxyundecyltrimethoxysilane, and its CAS number is 1196453-35-6.

[0069] Example 4

[0070] The preparation method of the PET composite film comprises the following steps:

[0071] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0072] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0073] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0074] The PVB adhesive comprises the following components in parts by mass:

[0075] PVB 10 parts

[0076] 2 parts of silane coupling agent

[0077] 100 parts of propylene glycol methyl ether;

[0078] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0079] The silane coupling agent is O-(propynyl)-N-(triethoxysilyl) methyl carbamate, and its CAS number is 870987-68-1.

[0080] Example 5

[0081] The preparation method of the PET composite film comprises the following steps:

[0082] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0083] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0084] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0085] The PVB adhesive comprises the following components in parts by mass:

[0086] PVB 10 parts

[0087] 2 parts of silane coupling agent

[0088] 100 parts of propylene glycol methyl ether;

[0089] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0090] The silane coupling agent is 3-(methacryloyloxy)propyltrimethoxysilane, and its CAS number is 2530-85-0.

[0091] Example 6

[0092] The preparation method of the PET composite film comprises the following steps:

[0093] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0094] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0095] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0096] The PVB adhesive comprises the following components in parts by mass:

[0097] PVB 10 parts

[0098] 2 parts of silane coupling agent

[0099] 100 parts of propylene glycol methyl ether;

[0100] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0101] The silane coupling agent is isocyanatepropyltriethoxysilane, with a CAS number of 24801-88-5.

[0102] Example 7

[0103] The preparation method of the PET composite film comprises the following steps:

[0104] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0105] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0106] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0107] The PVB adhesive comprises the following components in parts by mass:

[0108] PVB 10 parts

[0109] 2 parts of silane coupling agent

[0110] 100 parts of propylene glycol methyl ether;

[0111] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0112] The silane coupling agent is vinyltriethoxysilane, and its CAS number is 78-08-0.

[0113] Example 8

[0114] The preparation method of the PET composite film comprises the following steps:

[0115] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0116] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0117] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0118] The PVB adhesive comprises the following components in parts by mass:

[0119] PVB 10 parts

[0120] 2 parts of silane coupling agent

[0121] 100 parts of propylene glycol methyl ether;

[0122] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0123] The silane coupling agent is bis(3-trimethoxysilylpropyl)amine, and its CAS number is 82985-35-1.

[0124] Example 9

[0125] The preparation method of the PET composite film comprises the following steps:

[0126] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0127] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0128] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0129] The PVB adhesive comprises the following components in parts by mass:

[0130] PVB 10 parts

[0131] 2 parts of silane coupling agent

[0132] 100 parts of propylene glycol methyl ether;

[0133] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0134] The silane coupling agent is diethylenetriaminopropyltrimethoxysilane, and its CAS number is 35141-30-1.

[0135] Example 10

[0136] The preparation method of the PET composite film comprises the following steps:

[0137] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0138] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0139] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0140] The PVB adhesive comprises the following components in parts by mass:

[0141] PVB 10 parts

[0142] 2 parts of silane coupling agent

[0143] 100 parts of propylene glycol methyl ether;

[0144] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0145] The silane coupling agent is [3-(triethoxysilyl)propyl]urethane, and its CAS number is 17945-05-0.

[0146] The bonding strength of the PET composite films of Examples 1 to 10 was tested according to the test standard of GB / T 2790-1995. The test results are shown in Table 1.

[0147] Table 1 Effect of different silane coupling agents on the bonding strength of PVB adhesive project serial number Silane coupling agent CAS number Bonding strength (N / cm) Example 1 S1 116047-42-8 22.85 Example 2 S3 13822-56-5 46.03 Example 3 S11 1196453-35-6 20.72 Example 4 S12 870987-68-1 22.11 Example 5 S16 2530-85-0 21.42 Example 6 S22 24801-88-5 41.72 Example 7 S23 78-08-0 21.48 Example 8 S26 82985-35-1 42.32 Example 9 S29 35141-30-1 44.06 Example 10 S30 17945-05-0 22.25

[0148] The table above shows that the bond strength between PVB adhesive and PET is higher when the silane coupling agent contains amine or isocyanate groups. Specifically, when the silane coupling agent is 3-aminopropyltrimethoxysilane (S3, CAS No. 13822-56-5), the bond strength reaches 46.03 N / cm, which is higher than the diethylenetriaminopropyltrimethoxysilane coupling agent (S29, CAS No. 35141-30-1), which has a higher amine content.

[0149] Example 11

[0150] The preparation method of the PET composite film comprises the following steps:

[0151] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0152] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0153] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0154] The PVB adhesive comprises the following components in parts by mass:

[0155] PVB 10 parts

[0156] 0.11 parts of silane coupling agent

[0157] 100 parts of propylene glycol methyl ether;

[0158] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0159] The silane coupling agent is 3-aminopropyltrimethoxysilane, and its CAS number is 13822-56-5.

[0160] Example 12

[0161] The preparation method of the PET composite film comprises the following steps:

[0162] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0163] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0164] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0165] The PVB adhesive comprises the following components in parts by mass:

[0166] PVB 10 parts

[0167] 0.33 parts of silane coupling agent

[0168] 100 parts of propylene glycol methyl ether;

[0169] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0170] The silane coupling agent is 3-aminopropyltrimethoxysilane, and its CAS number is 13822-56-5.

[0171] Example 13

[0172] The preparation method of the PET composite film comprises the following steps:

[0173] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0174] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0175] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0176] The PVB adhesive comprises the following components in parts by mass:

[0177] PVB 10 parts

[0178] 0.55 parts of silane coupling agent

[0179] 100 parts of propylene glycol methyl ether;

[0180] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0181] The silane coupling agent is 3-aminopropyltrimethoxysilane, and its CAS number is 13822-56-5.

[0182] Example 14

[0183] The preparation method of the PET composite film comprises the following steps:

[0184] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0185] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0186] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0187] The PVB adhesive comprises the following components in parts by mass:

[0188] PVB 10 parts

[0189] 1.11 parts of silane coupling agent

[0190] 100 parts of propylene glycol methyl ether;

[0191] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0192] The silane coupling agent is 3-aminopropyltrimethoxysilane, and its CAS number is 13822-56-5.

[0193] Example 15

[0194] The preparation method of the PET composite film comprises the following steps:

[0195] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0196] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0197] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0198] The PVB adhesive comprises the following components in parts by mass:

[0199] PVB 10 parts

[0200] 1.68 parts of silane coupling agent

[0201] 100 parts of propylene glycol methyl ether;

[0202] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0203] The silane coupling agent is 3-aminopropyltrimethoxysilane, and its CAS number is 13822-56-5.

[0204] Example 16

[0205] The preparation method of the PET composite film comprises the following steps:

[0206] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0207] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0208] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0209] The PVB adhesive comprises the following components in parts by mass:

[0210] PVB 10 parts

[0211] 0.11 parts of silane coupling agent

[0212] 100 parts of propylene glycol methyl ether;

[0213] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0214] The silane coupling agent is diethylenetriaminopropyltrimethoxysilane, and its CAS number is 35141-30-1.

[0215] Example 17

[0216] The preparation method of the PET composite film comprises the following steps:

[0217] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0218] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0219] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0220] The PVB adhesive comprises the following components in parts by mass:

[0221] PVB 10 parts

[0222] 0.33 parts of silane coupling agent

[0223] 100 parts of propylene glycol methyl ether;

[0224] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0225] The silane coupling agent is diethylenetriaminopropyltrimethoxysilane, and its CAS number is 35141-30-1.

[0226] Example 18

[0227] The preparation method of the PET composite film comprises the following steps:

[0228] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0229] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0230] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0231] The PVB adhesive comprises the following components in parts by mass:

[0232] PVB 10 parts

[0233] 0.55 parts of silane coupling agent

[0234] 100 parts of propylene glycol methyl ether;

[0235] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0236] The silane coupling agent is diethylenetriaminopropyltrimethoxysilane, and its CAS number is 35141-30-1.

[0237] Example 19

[0238] The preparation method of the PET composite film comprises the following steps:

[0239] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0240] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0241] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0242] The PVB adhesive comprises the following components in parts by mass:

[0243] PVB 10 parts

[0244] 1.11 parts of silane coupling agent

[0245] 100 parts of propylene glycol methyl ether;

[0246] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0247] The silane coupling agent is diethylenetriaminopropyltrimethoxysilane, and its CAS number is 35141-30-1.

[0248] Example 20

[0249] The preparation method of the PET composite film comprises the following steps:

[0250] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0251] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 100 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0252] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0253] The PVB adhesive comprises the following components in parts by mass:

[0254] PVB 10 parts

[0255] 1.68 parts of silane coupling agent

[0256] 100 parts of propylene glycol methyl ether;

[0257] The PVB has a hydroxyl content of about 15%, a polymerization degree in the range of 499 to 2499, an average polymerization degree of about 800 to 1000, and PVB with a polymerization degree below 800 accounts for about 40%. Furthermore, PVB with a polymerization degree below 600 accounts for about 10%.

[0258] The silane coupling agent is diethylenetriaminopropyltrimethoxysilane, and its CAS number is 35141-30-1.

[0259] The bonding strength of the PET composite films of Examples 11 to 20 was tested according to the test standard of GB / T 2790-1995. The test results are shown in Table 2.

[0260] Table 2 Effect of different weight fractions of silane coupling agent on the bonding strength of PVB adhesive .

[0261] Table 2 shows that when the silane coupling agent is 3-aminopropyltrimethoxysilane (S3) or diethylenetriaminepropyltrimethoxysilane (S29), the PET composite film exhibits high bonding strength over a wide range, regardless of whether the silane coupling agent dosage is 0.09wt% or 1.5wt%, or any value in between. Table 2 further confirms that the PVB adhesive containing 3-aminopropyltrimethoxysilane (S3) has higher bonding strength to PET than the PVB adhesive containing diethylenetriaminepropyltrimethoxysilane (S29), indicating that the primary amine plays a dominant role in the bonding process.

[0262] Example 21

[0263] The preparation method of the PET composite film comprises the following steps:

[0264] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0265] S2, roll-coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 123 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0266] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0267] The PVB adhesive comprises the following components in parts by mass:

[0268] PVB 10 parts

[0269] 1.5 parts of silane coupling agent

[0270] G12 5 servings

[0271] 100 parts of propylene glycol methyl ether;

[0272] The PVB has a hydroxyl content of about 18% and a molecular polymerization degree of about 1800.

[0273] The silane coupling agent is diethylenetriaminopropyltrimethoxysilane, and its CAS number is 35141-30-1.

[0274] The G12 is a glass flake with a diameter of 600 μm and a thickness of 1.0~1.3 μm.

[0275] Example 22

[0276] The preparation method of the PET composite film comprises the following steps:

[0277] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0278] S2, roller coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 126 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0279] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0280] The PVB adhesive comprises the following components in parts by mass:

[0281] PVB 10 parts

[0282] 1.5 parts of silane coupling agent

[0283] Zeolite 13X 5 parts

[0284] 100 parts of propylene glycol methyl ether;

[0285] The PVB has a hydroxyl content of about 18% and a molecular polymerization degree of about 1800.

[0286] The silane coupling agent is diethylenetriaminopropyltrimethoxysilane, and its CAS number is 35141-30-1.

[0287] The Zeolite 13X is a zeolite powder with a particle size of 2 μm.

[0288] Comparative Example 1

[0289] The preparation method of the PET composite film comprises the following steps:

[0290] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0291] S2, roll-coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 129 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0292] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0293] The PVB adhesive comprises the following components in parts by mass:

[0294] PVB 10 parts

[0295] 1.5 parts of silane coupling agent

[0296] 100 parts of propylene glycol methyl ether;

[0297] The PVB has a hydroxyl content of about 18% and a molecular polymerization degree of about 1800.

[0298] The silane coupling agent is diethylenetriaminopropyltrimethoxysilane, and its CAS number is 35141-30-1.

[0299] Comparative Example 2

[0300] The preparation method of the PET composite film comprises the following steps:

[0301] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0302] S2, roll-coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 99 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0303] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0304] The PVB adhesive comprises the following components in parts by mass:

[0305] PVB 10 parts

[0306] 1.5 parts of silane coupling agent

[0307] 100 parts of propylene glycol methyl ether;

[0308] The PVB has a hydroxyl content of about 18% and a molecular polymerization degree of about 1800.

[0309] The silane coupling agent is diethylenetriaminopropyltrimethoxysilane, and its CAS number is 35141-30-1.

[0310] The following 24-hour water vapor transmission rate test was conducted on the PET composite films of Examples 21 and 22 and Comparative Examples 1 and 2 according to the test standard of GB / T 26253-2010. The test results are shown in Table 3.

[0311] Table 3 Effect of different fillers on water vapor transmission rate of PET composite film .

[0312] As can be seen from Table 3, the thickness of the PVB adhesive coating has little effect on the water vapor permeability of the PET composite film; however, the filler has a significant effect on the water vapor permeability of the PET composite film. When fillers are added to the PVB adhesive, the water vapor permeability of the composite film is significantly lower.

[0313] Example 23

[0314] The preparation method of the PET composite film comprises the following steps:

[0315] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0316] S2, roll-coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 83 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0317] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0318] The PVB adhesive comprises the following components in parts by mass:

[0319] PVB 10 parts

[0320] 1.5 parts of silane coupling agent

[0321] 10XL 5 servings

[0322] 100 parts of propylene glycol methyl ether;

[0323] The PVB has a hydroxyl content of about 10% and a molecular polymerization degree of about 1800.

[0324] The silane coupling agent is diethylenetriaminopropyltrimethoxysilane, and its CAS number is 35141-30-1.

[0325] The 10XL is a glass flake with a diameter of 3300 μm and a thickness of 0.3 μm.

[0326] Example 24

[0327] The preparation method of the PET composite film comprises the following steps:

[0328] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on both sides of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0329] S2, roll-coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 147 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0330] S3. Hot-press the two surfaces of the PET film with a PVB film having a thickness of 0.5 mm to obtain a PET composite film having a structure of PVB-adhesive-PET-adhesive-PVB; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0331] The PVB adhesive comprises the following components in parts by mass:

[0332] PVB 10 parts

[0333] 1.5 parts of silane coupling agent

[0334] 10XL 5 servings

[0335] 100 parts of propylene glycol methyl ether;

[0336] The PVB has a hydroxyl content of about 10% and a molecular polymerization degree of about 1800.

[0337] The silane coupling agent is diethylenetriaminopropyltrimethoxysilane, and its CAS number is 35141-30-1.

[0338] The 10XL is a glass flake with a diameter of 3300 μm and a thickness of 0.3 μm.

[0339] Comparative Example 3

[0340] The preparation method of the PET composite film comprises the following steps:

[0341] S1. Provide a PET film with a thickness of 2 mm and perform surface corona treatment on one side of the PET film; in this step, the output power of the corona treatment equipment is 5 kW and the treatment time is 20 min;

[0342] S2, roll-coating PVB adhesive on the corona-treated surface of the PET film, and then drying it; in this step, the coating thickness of the PVB adhesive is 127 μm; the drying temperature is 95° C., and the drying time is 10 min;

[0343] S3. Hot-pressing the PET film and a PVB film with a thickness of 0.5 mm to obtain a PET composite film; in this step, the hot-pressing temperature is 120° C., the pressure is 1.0 MPa, and the hot-pressing time is 100 s.

[0344] The PVB adhesive comprises the following components in parts by mass:

[0345] PVB 10 parts

[0346] 1.5 parts of silane coupling agent

[0347] 100 parts of propylene glycol methyl ether;

[0348] The PVB has a hydroxyl content of about 10% and a molecular polymerization degree of about 1800.

[0349] The silane coupling agent is diethylenetriaminopropyltrimethoxysilane, and its CAS number is 35141-30-1.

[0350] The following 24-hour water vapor transmission rate test was conducted on the PET composite films of Examples 23 and 24 and Comparative Example 3 in accordance with the test standard of GB / T 26253-2010. The test results are shown in Table 4.

[0351] Table 4 Effect of different fillers on water vapor transmission rate of PET composite film .

[0352] As can be seen from Table 4, fillers have a significant effect on the water vapor transmission rate of PET composite films. When fillers are added to the PVB adhesive, the water vapor transmission rate of the composite film is even lower. When the PVB adhesive containing fillers is coated on both sides of the PET, the water vapor transmission rate is further reduced.

Claims

1. A method for preparing a PET composite film, comprising the following steps: S1. Providing a PET film, and performing surface corona treatment on one or both sides of the PET film; S2, the corona treated surface of the PET film is roll-coated with PVB adhesive, followed by drying; S3, hot-pressing and laminating one or both sides of the PET film with a flexible encapsulation film to obtain a PET composite film; The PVB adhesive comprises the following components in parts by mass: PVB 5~20 parts Silane coupling agent 0.3~10 parts 90-100 parts of solvent; The solvent is selected from one or more of methanol, ethanol, butanone, propylene glycol methyl ether, propylene glycol methyl ether acetate, and toluene; The PVB has a hydroxyl content of 8-20% and a polymerization degree of 499-2499.

2. The method for preparing a PET composite film according to claim 1, wherein: The PVB adhesive further contains 2 to 30 parts by mass of a translucent filler, and the translucent filler is selected from one or more of transparent glass flakes, PPO film flakes, transparent ceramics, glass powder, glass fiber, transparent montmorillonite, transparent mica, fumed silica, amorphous silica, quartz sand, quartz powder, nano-silica, zeolite, transparent alumina ceramics, magnesium oxide transparent ceramics, yttrium oxide transparent ceramics, aluminum magnesium spinel transparent ceramics, aluminum nitride transparent ceramics, aluminum oxynitride transparent ceramics, transparent PLZT electro-optical ceramics, yttrium aluminum garnet laser transparent ceramics, and transparent scintillating ceramics.

3. The method for preparing a PET composite film according to claim 2, wherein: When the light-transmitting filler is spherical, the particle size is 10-800 μm; when the light-transmitting filler is flake-shaped, the flake size is 10-4000 μm and the thickness is 1 nm-30 μm.

4. The method for preparing a PET composite film according to claim 1, wherein: The silane coupling agent is selected from one or more of amino silane coupling agents, isocyanate silane coupling agents, and carbamate silane coupling agents.

5. The method for preparing a PET composite film according to claim 1, wherein: The amino-based silane coupling agent has one to three amino groups, and the amino groups are primary, secondary or tertiary amino groups.

6. The method for preparing a PET composite film according to claim 1, wherein: The coating thickness of the PVB adhesive is 100-800 μm.

7. The method for preparing a PET composite film according to claim 1, wherein: The flexible packaging film is selected from one of PVB film, EVA film or POE film.

8. The method for preparing a PET composite film according to claim 1, wherein: In step S1, the output power of the corona treatment equipment is 2-6 kW, and the treatment time is 15-30 min.

9. The method for preparing a PET composite film according to claim 1, wherein: In step S2, the drying temperature is 85-110° C., and the drying time is 5-10 minutes.

10. The method for preparing a PET composite film according to claim 1, wherein: In step S3, the hot pressing temperature is 100-150° C., the pressure is 0.5-2.0 MPa, and the hot pressing time is 30-100 seconds.

Citation Information

Cited By

  • Hydrophilic-hydrophobic double-sided synchronous processing device and method for solar photovoltaic backboard

    CN121815793A